Kinematics of the turning kick - measurements obtained in testing well-trained taekwon-do athletes - Wasik, J.; Shan, G. (Archives of Budo, 2015)
Background and Study Aim: The aim of the paper is the influence of selected kinematic factors on the turning kick technique. This issue is practically relevant in the traditional version of taekwon-do, where an effectively performed strike may divulge the winner. Material and Method: Using 3D motion capture technology, six International Taekwon-do Federation athletes were tested. Biomechanical parameters related to range of motion, kick power and kick time were applied in the analyses. The athletes executed the turning kick three times in a way typically applied in a board breaking kick. The quantification focused on the speed changes related to kicking leg extension, the maximum knee and foot velocities in the Cartesian coordinate system and the total time of kick execution. The descriptive statistics (i.e. average values and the standard deviations) and correlation analysis were applied in data analysis. Results: The results have shown that the effect of the kick is mainly represented by component of kick foot velocity in frontal- and lateral-directions. The correlation analyses unveil that the maximal knee speeds reached in frontal- and lateral-directions as well as foot take-off velocity in frontal- and vertical-directions are highly correlated to kick foot effectiveness (r = 0.60 to 0.87). The analysis of velocity development in relation to kick leg extension divulges that the maximal velocity occurs around 80% of a full leg extension. Conclusion: For increasing kick effectiveness, athletes should work on the foot take-off velocity, the dynamics of the knee motion and consider the optimum kick length for kicking power maximization.